Beyond borders: Exploring the challenges of refugee children in Saudi Arabia and Turkey - Thoraya A. bin Kadasah; Ghadah S. Alsedrani (PLoS ONE, 2025)
The number of displaced individuals worldwide is increasing due to revolutions, wars, and economic crises. However, research on the educational, social, and cultural challenges facing refugee children is limited. Thus, this study aimed to investigate these challenges in Saudi Arabia and Turkey by focusing on refugee children’s adaptation to new cultural and social norms. Using quantitative methods, we surveyed 418 parents of refugee children living in Saudi Arabia and Turkey and examined variables such as gender, residency, and parental education level. The findings indicated that the challenges refugee children faced were significantly associated with parental education levels, but not with country of residence. Specific cultural challenges also emerged, highlighting the struggles faced by refugees worldwide and underlining the crucial need for cultural acceptance and resources to facilitate refugee children’s participation in social and cultural settings and their integration into host societies. These findings carry important implications for policymakers in Turkey, Saudi Arabia, and comparable settings, specifically concerning the need for policy reforms and targeted support to facilitate the integration of refugee children into new educational and cultural contexts. This study contributes significantly to current knowledge in that it examined the educational, social, and cultural challenges facing refugee children within the Saudi Arabian context, which had remained largely unexplored in the existing relevant literature, filling a gap in the extant research. See Graphical Abstract.